Drying curve simulation and LF-NMR online monitor of water state in ursolic acid loaded chitosan nanoparticles during microwave freeze drying - Ren, Xing; Duan, Xu; Cao, Weiwei; Zhao, Lujie; Ren, Guangyue; Liu, Panpan (International Journal of Agricultural and Biological Engineering, 2023)
Changes in various states of water in ursolic acid (UA) loaded chitosan nanoparticles were assessed using low-field nuclear magnetic resonance (LF-NMR) during microwave freeze drying (MFD) process, and six thin-layer models were applied to simulate the drying kinetics. UA nanoparticles were dried at different microwave power densities (1 W/g, 2 W/g and 4 W/g). The results showed that three water fractions with different transverse relaxation times (T2) were detected in fresh UA nanoparticles. The T2 relaxation time of water decreased significantly with the increase of drying time at different microwave power densities. And the mutual migration and transformation of water in different states during the drying process of chitosan nanoparticles occurred. Furthermore, mathematical model analysis showed that the Page model provided the best description during the process of UA nanoparticle dried by MFD. The Page model can better simulate the drying kinetics of chitosan nanoparticles dried by MFD, and LF-NMR technology can monitor the changes in water status of UA nanoparticles. The results revealed that LF-NMR can monitor the changes of water in UA nanoparticles during the drying process. Keywords: microwave, drying, chitosan nanoparticles, water distribution DOI: 10.25165/j.ijabe.20231604.7519 Citation: Ren X, Duan X, Cao W W, Zhao L J, Ren G Y, Liu P P. Drying curve simulation and LF-NMR online monitor of water state in ursolic acid loaded chitosan nanoparticles during microwave freeze drying. Int J Agric & Biol Eng, 2023; 16(4): 263－268.